RFID Demystified: Part 3. Company Case Studies. - Wilding, Richard D.; Delgardo, Tiago (The Chartered Institute of Logistics and Transport, 2004)
In the previous two parts of RFID Demystified we have discussed the technology, possible benefits and areas of application for with Radio Frequency Identification (RFID) systems. In this final part we review Company Case-Studies of those who have decided to apply the technology within their organisation. It will be seen that considerable benefits are being experienced within some organisations, pilot applications are increasing our learning and providing a foundation for the future success of projects in this area.